2014
DOI: 10.1017/s1368980014001438
|View full text |Cite
|
Sign up to set email alerts
|

Association of coffee drinking with all-cause mortality: a systematic review and meta-analysis

Abstract: Objective: We aimed to use the meta-analysis method to assess the relationship between coffee drinking and all-cause mortality. Design: Categorical and dose-response meta-analyses were conducted using random-effects models. Setting: We systematically searched and identified eligible literature in the PubMed and Scopus databases. Subjects: Seventeen studies including 1 054 571 participants and 131 212 death events from all causes were included in the present study. Results: Seventeen studies were included and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 61 publications
4
18
0
6
Order By: Relevance
“…In animal models of PD, treatment with caffeine ameliorated oxidative stress, restored the depletion of midbrain and striatal dopamine, prevented decline in motor activities and muscular strength, and improved norepinephrine level . All‐cause mortality studies suggest that the inverse association with caffeine may be attributable to caffeine's protection against cardiovascular disease and some cancers . We did not assess specific causes of death among patients because of sample size limitations, but we did control for these comorbidities when assessing all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of PD, treatment with caffeine ameliorated oxidative stress, restored the depletion of midbrain and striatal dopamine, prevented decline in motor activities and muscular strength, and improved norepinephrine level . All‐cause mortality studies suggest that the inverse association with caffeine may be attributable to caffeine's protection against cardiovascular disease and some cancers . We did not assess specific causes of death among patients because of sample size limitations, but we did control for these comorbidities when assessing all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…For total coffee, the previous meta‐analysis indicated that the health‐promoting effect of coffee was associated with female rather than male consumers. We also found similar results for low coffee consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that consuming a moderate amount of caffeine has a protective effect against cancer [12], diabetes mellitus type 2 [13], inflammatory diseases and pain [14], Parkinson's and related neurodegenerative diseases [15], cardiovascular disease [16], and stroke [17]. Light to moderate caffeine intake has also been found to be associated with reduced risk of death [18] from all causes, including suicide [19].…”
Section: Introductionmentioning
confidence: 99%